Learning with and about Digital Technology in Later Life: A Socio-Material Perspective - Rebekka Rohner; Lisa Hengl; Vera Gallistl; Franz Kolland (MDPI AG, 2021)
Literature has widely explored the learning processes with information and communication technology (ICT) in later life, mostly focusing on the individual learner rather than materialities-such as smartphones, notepads, and handouts. The aim of this paper is to introduce a socio-material perspective by focusing on the question: What role do materialities play in digital learning processes in later life? This paper draws upon a situation analysis of data from a qualitative multi-perspective study. Researchers conducted participatory observations of five ICT courses for older adults in Austria and semi-structured interviews with seven trainers and nine older participants (61-81 years). By identifying three social worlds (digital devices, education, and participants' everyday lives), the findings show how ICT-learning processes are embedded in the everyday lives of older adults and include not only digital, but also everyday materialities, such as pens, paper and books. These material convoys of digital learning in later life are vital in facilitating successful technology appropriation in later life.